2004
DOI: 10.2466/pr0.94.3c.1253-1260
|View full text |Cite
|
Sign up to set email alerts
|

The Primacy of Beauty in Judging the Aesthetics of Objects

Abstract: The conceptual structure of the aesthetics of objects was investigated. To this end, associative namings for the word "aesthetics" were collected from 311 nonartist German college students in a timed verbal association task. 590 different adjectives were produced, depicting diversification of the concept. The adjective "beautiful" was given by more than 90% of the participants. The adjective "ugly" was the second most frequent naming, used by almost half of the students. All other namings were markedly less fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
103
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(114 citation statements)
references
References 8 publications
4
103
2
Order By: Relevance
“…These theories often relied on psychophysical studies aiming to identify particular stimulus properties that induce aesthetic experience. Studies of the so-called 'golden section' in abstract geometrical figures provide one example (McManus & Weatherby, 1997), but similar approaches have been used with paintings (Jacobsen & Hofel 2002;Jacobsen, 2004;Jacobsen, Buchta, Kohler & Schroger, 2004;Whissell, 1980;McManus, 1980). Such studies generally suggest that aesthetic experience depends on compositional arrangement between parts of the stimulus, and between individual parts and the whole.…”
Section: Introductionmentioning
confidence: 99%
“…These theories often relied on psychophysical studies aiming to identify particular stimulus properties that induce aesthetic experience. Studies of the so-called 'golden section' in abstract geometrical figures provide one example (McManus & Weatherby, 1997), but similar approaches have been used with paintings (Jacobsen & Hofel 2002;Jacobsen, 2004;Jacobsen, Buchta, Kohler & Schroger, 2004;Whissell, 1980;McManus, 1980). Such studies generally suggest that aesthetic experience depends on compositional arrangement between parts of the stimulus, and between individual parts and the whole.…”
Section: Introductionmentioning
confidence: 99%
“…Aesthetic objects are described using specific labels, including but not limited to 'beauty' (Jacobsen et al, 2004). In the case of performing arts such as dance, the observer's aesthetic experience is presumably grounded in the responses of their neural sensory, motor and affective circuits to the expressive actions of the dancer's body.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, semantic analyses of the terms that people use to label aesthetic appreciation of different types of visual objects, including clothes and faces (Jacobsen et al, 2004;Augustin et al, 2012), music (Istok et al, 2009) and different literary genres (Knoop et al, 2016) have shown that the dimensions of beautifulness and ugliness were dominant across several domains. Nevertheless, other dimensions were relevant in specific domains, for example interestingness and suspensefulness in literature (Knoop et al, 2016).…”
Section: Limitations and Conclusionmentioning
confidence: 99%
“…In different groups of participants, these areas were stimulated on the left or right hemisphere. Following previous studies (Calvo-Merino et al, 2008;Cross et al, 2011;Cazzato et al, 2014), we focused on the aesthetic dimension of like-dislike ratings rather than on the objective dimension of beautiful vs. non-beautiful ratings (Augustin et al, 2012;Jacobsen et al, 2004;Knoop et al, 2016). Furthermore, to rule out the possibility that rTMS may induce a simple bias either towards preferring (or not preferring) the first image of a pair of stimuli by using a forced-choice aesthetic preference task (Calvo-Merino et al, 2010), we asked participants for explicit aesthetic ratings of how much they liked each stimulus.…”
Section: Introductionmentioning
confidence: 99%